GAMBARAN EFEK SAMPING PENAMBAHAN MORFIN INTRATEKAL PADA PASIEN SECTIO CAESAREA DENGAN ANESTESI SPINAL DI RUMAH SAKIT HERMINA PADANG TAHUN 2026 - Perdana Rizky; Tia Reza; Darmayanti Anita (Nusantara Hasana Journal, 2026)
Cesarean section (CS) is an obstetric surgical procedure that has seen a significant global increase. Post-CS patients commonly experience moderate-to-severe acute pain at the abdominal wall and uterine incision sites. A multimodal analgesia strategy effectively utilized to provide long-lasting pain relief is the administration of intrathecal morphine as an adjuvant to spinal anesthesia. Although proven effective in extending the pain-free interval, the use of intrathecal morphine carries risks of specific side effects that necessitate routine monitoring. To determine the side effect profile of intrathecal morphine adjuvant among patients undergoing Cesarean section (CS) under spinal anesthesia at Hermina Hospital Padang in 2026. This was a quantitative descriptive study utilizing a cross-sectional design. The sample comprised patients undergoing CS under spinal anesthesia with intrathecal morphine adjuvant at Hermina Hospital Padang in 2026 who met the inclusion and exclusion criteria. Data collection instruments included observation sheets and medical records to evaluate demographic characteristics and the incidence of postoperative side effects. The minimum required sample size was 30 samples. Regarding patient characteristics, the majority fell within the healthy reproductive age range of 20–35 years, accounting for 28 individuals (84.84%), most were primiparous (54.53%), and a majority of 19 patients (57.57%) had no prior history of CS. The most predominant side effect observed among respondents was nausea and vomiting, occurring in 8 cases (24.24%), followed by pruritus in 7 cases (21.21%). Additionally, a concurrent combination of nausea-vomiting and pruritus was observed in 4 cases (12.12%). Severe side effects, such as somnolence, urinary retention, and respiratory depression, were entirely absent among all respondents in this study. Conclusion: The administration of intrathecal morphine as an adjuvant to spinal anesthesia in CS patients at Hermina Hospital Padang in 2026 was shown to be relatively safe. The most frequently occurring side effects were mild-to-moderate, namely nausea-vomiting and pruritus, with no severe adverse effects reported.